Business ethics, social responsibility and corporate governance: Does the strategic management field really care about these concepts? - TAYŞİR, EYÜP AYGÜN (ELSEVIER SCIENCE BV, 2013)
In this study we aimed to understand the strategic management (SM) field's opinions about corporate governance, social responsibility and business ethics concepts. In order to realize our aim, we analyzed one of the most reputable journals in the field, the Strategic Management Journal (SMJ). Computer-aided content analysis of 908 articles published between 1998 and 2010 revealed that only 25 articles which focused on the relationship between corporate governance, social responsibility, business ethics and corporate performance/strategy concepts, appeared in SMJ. We also analyzed the methodology and major findings of these 25 articles and found that the SM field has been neglecting these concepts, though not totally ignoring them. The possible explanation of this negligence is also discussed.
Keywords: Business ethics; Social responsibility; Corporate governance; Strategy; Strategic management; FINANCIAL PERFORMANCE; SHAREHOLDER VALUE; STAKEHOLDERS